An expert system for the manufacturing design of precast concrete panels - Hufemia, Edwin P.; Pandey, P. C.; Duflou, Joost R.; Bohez, Erik L.J.; Partial, Asian Institute of Technology and Ramcar Inc. (Bangkok : Asian Institute of Technology, 1996)
The thesis described herein has demonstrated the applicability of expert systems for the design of precast concrete panel designs. An expert system named PreCast was developed and implemented to assist designers in determining and locating appropriate fixture types for a given panel configuration. Fifteen panel configurations and six attachment types are provided as design options. PreCast was developed using the AutoLISP programming language and interfaces with AutoCAD to produce design and drawing outputs similar to that obtained by the company using the present manual system. PreCast uses heuristic-type reasoning based on production rule mechanism in manipulating the knowledge contained in the knowledge base in deriving design solutions. The information embodied in PreCast was obtained from the design department of M.C.S. International Co., Ltd.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Advanced Technologies
Thesis (M. Eng.) - Asian Institute of Technology, 1996
Keywords: CAD/CAM systems